Economic and Business Dimensions: The Extent of Globalization of Software Innovation. - Arora, Ashish; Drev, Matej; Forman, Chris (Communications of the ACM, 2009)
The article discusses the question of whether or not innovation within the computer software industry has become a global trend. Although software production occurs in many countries, the authors state, innovative software is not created everywhere. Topics include the increasing levels of software development in the country of India, software that is meant to be sold as a standalone product, software that is developed as a service, and an analysis of patent data related to computer software development.